A Note on Vickrey's Comment. - Larson, Kermit D.; Schattke, R. W. (The Accounting Review, 1975)
Presents a reply to Vickrey's comment on the study on the additivity of current cash equivalent. Rejection of the possibility that CCE could be defined as numerosity; Argument that purchasing power is nonadditive; Recommendations for future research.